Studies in Population Genetics - Carmen Fusté, M. (IntechOpen, 2012)
This book deals with central concepts in population genetics, describing the main evolutionary processes that influence the allele frequency distribution and change. The different chapters discuss topics such as population size and structure, migration, inbreeding and interbreeding, mechanisms of extinction and speciation, along with different data techniques and molecular methods used for detecting DNA sequence variation in the study of genetic polymorphisms. Part of the book includes statistical and computational methods commonly used to process population genetics data, which constitute an essential tool for understanding the concepts discussed. The book will be a useful reference for graduate students and researchers working on population genetics, and other related areas including microbiology, genetics, molecular biology, ecology, anthropology and others.